2020
DOI: 10.1093/gigascience/giaa134
|View full text |Cite
|
Sign up to set email alerts
|

Accurate assembly of the olive baboon (Papio anubis) genome using long-read and Hi-C data

Abstract: Background Baboons are a widely used nonhuman primate model for biomedical, evolutionary, and basic genetics research. Despite this importance, the genomic resources for baboons are limited. In particular, the current baboon reference genome Panu_3.0 is a highly fragmented, reference-guided (i.e., not fully de novo) assembly, and its poor quality inhibits our ability to conduct downstream genomic analyses. Findings Here we pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…These primary analyses provided approximately 10 million high-quality, 100 bp paired end reads per sample in FASTQ format, which were then used for secondary data analyses performed with a pipeline of software tools available from Partek Flow (Partek Inc.). These secondary analyses included steps such as additional filtering of reads to base quality of Phred 30, and alignment of reads to the publicly available assembly of the olive baboon genome, Panubis 1.0 ( Batra et al., 2020 ), with the RNA-Seq aligner pipeline STAR 2.5.3a ( Dobin et al., 2013 ), post alignment quality assessment, and transcript abundance estimation according to Ensembl transcriptome annotation by expectation- maximization algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…These primary analyses provided approximately 10 million high-quality, 100 bp paired end reads per sample in FASTQ format, which were then used for secondary data analyses performed with a pipeline of software tools available from Partek Flow (Partek Inc.). These secondary analyses included steps such as additional filtering of reads to base quality of Phred 30, and alignment of reads to the publicly available assembly of the olive baboon genome, Panubis 1.0 ( Batra et al., 2020 ), with the RNA-Seq aligner pipeline STAR 2.5.3a ( Dobin et al., 2013 ), post alignment quality assessment, and transcript abundance estimation according to Ensembl transcriptome annotation by expectation- maximization algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…; electronic supplementary material, table S1). Trimmed reads were mapped to the Panubis 1.0 genome (GCA_008728515.1) using the STAR 2pass aligner [113,114]. Finally, we generated gene-level counts royalsocietypublishing.org/journal/rstb Phil.…”
Section: (C) Genomic Data Generationmentioning
confidence: 99%
“…After we started to analyze the GNP sample, an additional baboon reference genome became available (Panubis1.0 [ 53 ]). Structural differences between the Panu_3.0 and Panubis1.0 assemblies have been highlighted.…”
Section: Methodsmentioning
confidence: 99%
“…The recombination map produced using a block penalty value of 5 was used as those were the rates focused on in the Robinson et al [ 78 ] study. Recombination rates for the Panu_3.0 assembly from the Panu_2.0 assembly were generated using the liftOver chain provided by Robinson et al Furthermore, regions which were found to be erroneously assembled in Panu_3.0 [ 53 ] were masked for both aforementioned analyzes.…”
Section: Methodsmentioning
confidence: 99%